Perspectivas e desafios sobre a temática consumismo infantil: os olhares de professoras dos anos iniciais do ensino fundamental - Lamana, Isabel Cristina Alves Cardoso (2020)
Education for a conscious consuming and for a socio-environmental responsibility should be present in pedagogical practices developed during Elementary School. However, this theme is still absent in schools. This research aimed to investigate and characterize the teaching process with “child consumerism” topic in pedagogical practices of teachers from early years education in São Carlos-SP. Methodologically it involved field research that included the researcher's diary, documental analysis and semi-structured interviews. Two managers and five effective teachers from the 5th grade participated in the research. Data analysis was performed using the content analysis technique and the emerging categories were "the concept of child consumerism" and "the place child consumerism in the teacher’s work". About the first, the analyzes indicate that all teachers and managers had already heard about child consumerism, however they showed different views on the concept. Regarding the place of the theme in the teachers' daily work, the majority declared observing consumerist situations among students, but the work with the theme is carried out sporadically and punctually throughout the academic year. Some factors related to this are the feeling of lack of preparation to include the subject with children and the lack of time, directly linked to the priority given to the contents of Portuguese and Mathematics in the early years. We didn’t identify specific projects on consumerism in these schools and, although there are projects linked to the environmental theme in a more broad sense, such practices are linked to recycling and/or specifically follow the teaching materials. However, although the study indicates the absence of regular work on child consumerism in the investigated realities, all participants recognize the importance of discussing the topic with children. We expect that this work will contribute to the discussion of the pedagogical practices of the early years in relation to conscious consumption and encourage new research on the topic. The results also point to the absence of projects about this theme in schools, although there are some projects related to the environmental theme in a broader way. In this sense, our study indicates the absence of a regular work about child consumerism in the investigated realities. When existing, such practices are associated with recycling and/or specifically follow the proposals of the teaching material. There is a lack of documents and some curricular proposals that guide them to work on Environmental Education. We hope this work can contribute to the discussion of pedagogical practices of the early years of education, as well as with the promotion of new researches about this topic.